Rapid Evidence Review on Remote Teaching and Learning - Pacitto, Julia; Hayat, Amal; Hinks, Jessica; Emerusenge, Aime Parfait; Ullah, Noor; Rabi, Asma (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to teaching practices and pedagogies for emergency remote learning. The main aim of this review is to provide education decision-makers, funders, and implementers (among others) with a clear understanding of the available global evidence on effective practices in teaching when students are educated remotely during emergencies, and to assess the relevance of this evidence for low- and middle-income contexts. The findings of the RER are organised by the following five themes: (i) instructional design for remote learning in emergency contexts; (ii) student engagement and interactivity in emergency remote teaching; (iii) assessment, feedback, and pedagogical adaptation in remote teaching during emergencies; (iv) well-being, ‘Maslow before Bloom’, and pedagogies of care in emergency remote teaching; (v) teacher training and support in remote teaching during crises. It also identifies critical gaps in the literature on emergency remote teaching and learning, and suggest avenues for future productive research to address these gaps. Keywords: Education in Emergencies, remote learning, pedagogy, teaching methods, EdTech, emergency remote teaching An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14967648 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1098 ZenodoArchiveConcept: 14967647
Keywords: _r:AddedByMyEducationEvidence

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

Using EdTech in Response to Climate Emergencies in Pakistan - Hayat, Amal; Mazari, Haani; Aslam, Nawaz (EdTech Hub, 2025)
This policy brief explores how EdTech can support a climate-resilient education system, drawing on insights from stakeholder consultations and EdTech Hub's research on learning continuity in response to climate emergencies following the 2022 Pakistan floods. While recovery efforts often focus on restoring physical infrastructure, we argue that a shift to long-term resilience against climate emergencies can be supported by strategic and contextually relevant use of EdTech. The brief highlights the importance of addressing the evolving needs of learners and teachers across all phases of emergencies through preparedness measures and cross-sectoral collaboration. Keywords: Pakistan floods; climate resilience; EdTech; Education in emergencies; South Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15851578 ZenodoArchiveConcept: 15851577 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7782171 10.53832/edtechhub.0160 10.53832/edtechhub.1129 2405685:333BJPIR
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

The Use of Interactive Whiteboards to Support Refugee Learning - Ramesh Vasudevan, Sharanya; Handigol, Apoorva (EdTech Hub, 2025)
This EdTech Hub rapid scan outlines the efficacy of interactive whiteboards (IWBs) to better understand the potential impact of investment in the digitisation of teaching and learning materials to enhance access to education and learning for refugee children. The focus is on research that can highlight any evidence on the efficacy of interactive whiteboards in low- and middle-income country (LMIC) contexts characterised by high numbers of school-age refugees, with Turkey as a key case study. The scan highlights important and valid considerations that can be applied to broader learnings around IWBs. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15692961 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1123 ZenodoArchiveConcept: 15692960
Keywords: _r:AddedByMyEducationEvidence

Summary: Out-of-School Children and Youth - A Rapid Evidence Review for the Southeast Asian Region - Afzal, Nimra; Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D’Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12819080 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1044 ZenodoArchiveConcept: 12819079
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

EdTech in Lao People's Democratic Republic: A Rapid Scan - Afzal, Nimra; Thang, Sarah; Tulivuori, Jukka; Thinley, Sangay; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive. Nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, and in this case, Lao People’s Democratic Republic (PDR). This report was originally written in February 2024. It is based primarily on desk research, with quality assurance provided by a country expert based at the Australian Council for Educational Research. Keywords: Ministry of Education and Sports; digital skills; training programmes; government expenditure; learning outcomes; disparities An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11118414 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1026 ZenodoArchiveConcept: 11118413
Keywords: _r:AddedByMyEducationEvidence

Summary: EdTech in Lao People's Democratic Republic - A Rapid Scan - Afzal, Nimra; Thang, Sarah; Tulivuori, Jukka; Thinley, Sangay; Mazari, Haani (EdTech Hub, 2024)
This document is a summary of a country scan on Lao Peoples Democratic Republic produced by EdTech Hub as part of the ASEAN-UK SAGE programme. EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Lao People's Democratic Republic. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12817771 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1039 ZenodoArchiveConcept: 12817770
Keywords: _r:AddedByMyEducationEvidence

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10610797 ZenodoArchiveConcept: 10610796 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1007 2339240:SZE9FBW4 2405685:IIAMD77T
Keywords: _r:AddedByMyEducationEvidence

Summary: EdTech for Out-of-School Children and Youth - A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D’Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This document is a summary of a rapid evidence review on EdTech for Out-of-School Children and Youth produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/.An output of the EdTech Hub, https://edtechhub.org/ An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12819080 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1044 ZenodoArchiveConcept: 12819079
Keywords: _r:AddedByMyEducationEvidence

EdTech for Education in Emergencies: A review of existing guidance and minimum standards - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Hayat, Amal; Emerusenge, Aime Parfait; Zazai, Rozina (EdTech Hub, 2024)
EdTech Hub is seeking to work with the education in emergencies (EiE) sector to develop quality standards and guidance relating to the effective implementation of educational technology (EdTech) in crisis contexts. To ensure that this work is genuinely meaningful and helpful, it is important to understand what guidance is already available in this space, and what effective guidance could look like. To do this, we reviewed existing guidance documents relating to the design and implementation of EdTech in emergency contexts, along with materials from adjacent disciplines such as humanitarian work and technology design and development. By identifying key commonalities and persistent gaps across these documents, we were able to suggest what future guidance relating to EdTech in emergencies should include, and how this guidance should be developed. Keywords: EdTech; education in emergencies; guidance; minimum standards An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14051241 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1068 ZenodoArchiveConcept: 14051240
Keywords: _r:AddedByMyEducationEvidence

EdTech in Vietnam: A Rapid Scan - Honda, Delanie; Halla, Ken; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Vietnam. This report was originally written in March 2024. It is based primarily on desk research, with quality assurance provided by country experts at Southeast Asian Ministers of Education Organization (SEAMEO) centres. Keywords: out-of-school children and youth; digital education; Southeast Asia; girls’ education; secondary education An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11445854 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1031 ZenodoArchiveConcept: 11445853
Keywords: _r:AddedByMyEducationEvidence

Summary: EdTech in Vietnam - A Rapid Scan - Honda, Delanie; Halla, Ken; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
This document is a summary of a country scan on XYZ produced by EdTech Hub as part of the ASEAN-UK SAGE programme. EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Vietnam. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12818950 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1041 ZenodoArchiveConcept: 12818949
Keywords: _r:AddedByMyEducationEvidence

EdTech in Timor-Leste: A Rapid Scan - Honda, Delanie; Thinley, Sangay; Thang, Sarah; Flam, Rebekka; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Timor-Leste. This report was originally written in February 2024. It is based primarily on desk research, with quality assurance provided by a country expert at the Australian Council for Educational Research. Keywords: out-of-school children and youth; girls' education; Southeast Asia; learners with special education needs and disabilities; digital education An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11118401 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1025 ZenodoArchiveConcept: 11118400
Keywords: _r:AddedByMyEducationEvidence

Summary: EdTech in Timor-Leste - A Rapid Scan - Honda, Delanie; Thinley, Sangay; Thang, Sarah; Flam, Rebekka; Mazari, Haani (EdTech Hub, 2024)
This document is a summary of a country scan on XYZ produced by EdTech Hub as part of the ASEAN-UK SAGE programme. EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Timor-Leste. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12817786 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1040 ZenodoArchiveConcept: 12817785
Keywords: _r:AddedByMyEducationEvidence

What is 'Nudging' and How Does it Change Behaviour in Education? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the behaviour change strategy of leveraging concise messages at strategic decision points (i.e., ‘nudging’) to influence the behaviour of a recipient towards a desired outcome. We focus on EdTech Hub’s work concerning nudge messaging. It builds on work from messaging interventions in Ghana and Kenya, linking these to the broader literature on the topic. It emphasises that although there is a strong and growing evidence base for nudge technologies, effective implementation remains dependent upon context-specific adaptation. It is not inevitable that nudge messaging interventions will lead to positive outcomes — indeed, outcomes are often mixed. It is therefore vital to understand the specific impacts of interventions on particular groups of recipients. We present findings and recommendations that should inform how nudging technologies in education are approached and what decision-makers need to consider in order to ensure uptake and minimise risks. Lastly, we explore areas that require further research, namely, the changing nature of nudging due to artificial intelligence, the safeguarding risks of nudging, persisting questions about cost-effectiveness, and how nudging can more specifically target learning. Keywords: Behavioural psychology; EdTech; education; messaging; nudging; participation An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10628960 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1011 ZenodoArchiveConcept: 10628959
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Cognitive and Learning Disabilities: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Afzal, Nimra (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with cognitive and learning disabilities. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. We discuss the nature of EdTech for learners living with cognitive and learning disabilities, the effectiveness of these initiatives, and barriers for accessing EdTech. The RER aims neither to advocate nor discourage the use of technology to support education for learners with coginitive and learning disabilities, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; cognitive disabilities; learning disabilities; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10987889 ZenodoArchiveConcept: 10987888 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1006 10.53832/edtechhub.1023 2339240:U7UE5PIN 2405685:B422KBGQ 2405685:HD58IXI3 2405685:PGRMI8NH
Keywords: _r:AddedByMyEducationEvidence; ⛔ No INSPIRE recid found

Cohort Learning Handbook - Nicholson, Bryony (EdTech Hub, 2024)
The Cohort Learning Handbook captures EdTech Hub’s approach to building cohorts on its Evidence-Led Entrepreneurship Course. The course aims to help entrepreneurs adopt and utilise evidence to learn and to scale their products and services. The Handbook is for individuals and organisations who support EdTech entrepreneurs (e.g., accelerators, entrepreneurship programmes, and funders). Building a cohort supports entrepreneurs to learn quickly and more confidently as a result of learning with, from, and alongside peers sharing the same experience. By ensuring that the learning journey is the most effective it can be, we ensure our work has the greatest impact. By facilitating a cohort journey for EdTech entrepreneurs, you can: - Leverage the unique power of a cohort to improve the learning experience and learning outcomes. - Diversify the support on offer. - Streamline and improve technical support that we often offer ventures. The handbook includes a list of resources and templates for you to use and covers a range of topics and practical suggestions from key principles and onboarding to graduation and supporting alumni. Keywords: cohort; community; learning; collective; incubators; accelerators An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13255974 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1052 ZenodoArchiveConcept: 13255973
Keywords: _r:AddedByMyEducationEvidence

EdTech in Nigeria: A Rapid Scan. An overview of EdTech policies and interventions in Nigeria with a focus on northern Nigeria - Ramesh Vasudevan, Sharanya; Oyedele, Oluwatomisin (EdTech Hub, 2024)
Commissioned as a Helpdesk request from the FCDO-funded Partnership for Learning for All in Nigeria (PLANE) project, this EdTech Hub rapid scan provides an overview of the EdTech landscape in Nigeria. Given the PLANE programme’s focus on northern Nigeria, this rapid scan also assesses state-level policies and infrastructural challenges in three northern Nigerian states — Jigawa, Kaduna, and Kano. Furthermore, this rapid scan builds on the evidence presented in the previous EdTech Hub rapid scan from 2020, which focused on all states and the situation before the Covid-19 pandemic. Keywords: EdTech; policies; interventions; northern Nigeria; Partnership for Learning for All in Nigeria An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11235144 ZenodoArchiveConcept: 11235143 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1029 10.53832/edtechhub.1030
Keywords: _r:AddedByMyEducationEvidence

EdTech in Cambodia: A Rapid Scan - Thinley, Sangay; Hayat, Amal; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These include policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, Cambodia. This report was originally written in January 2024. It is based primarily on desk research, with quality assurance provided by a country expert — an Education Specialist with the UNICEF Cambodia office. Keywords: out-of-school populations; girls and gender; Southeast Asia; learners with special educational needs and disabilities; primary education; secondary education An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10893092 ZenodoArchiveConcept: 10893091 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1020 2405685:Z7XKA7E8
Keywords: _r:AddedByMyEducationEvidence

Summary: EdTech in Cambodia - A Rapid Scan - Thinley, Sangay; Hayat, Amal; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
This document is a summary of a country scan on XYZ produced by EdTech Hub as part of the ASEAN-UK SAGE programme. EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Cambodia. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12817714 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1038 ZenodoArchiveConcept: 12817713
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11197419 ZenodoArchiveConcept: 11197418 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1027 10.53832/edtechhub.1028 2405685:DQ9GNC3J 2405685:M6A4ZHJ3
Keywords: _r:AddedByMyEducationEvidence

The Use of Technology to Promote Equity and Inclusion in Education in North and Northeast Kenya - Otieno, Jennifer; Kaye, Tom; Mbugua, Wanjiku (EdTech Hub, 2023)
Kenya has been lauded as having one of the most progressive and effective education systems in Africa. Significant investments in education funding, innovative technology-enabled approaches to improve teaching and learning, and committed leadership make Kenya an example for neighbours and others across the world. However, at a sub-national level, significant variances in education access and quality arise. While many improvements have been made to participation, quality, equity, and inclusion in education in Kenya, there are persistent disparities in access and outcomes for rural learners, girls, learners with disabilities, and other vulnerable populations. The North and Northeastern (N/NE) counties of Kenya are where some of the greatest disparities exist. Our research examines the context of N/NE Kenya to understand why these disparities exist, and how technology can play a role in increasing equity and inclusion in education in the region. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7781293 ZenodoArchiveConcept: 7781292 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7781293 10.53832/edtechhub.0159 2405685:GS45WQWR
Keywords: _r:AddedByZotZen

Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5774707 10.53832/edtechhub.0093 2339240:SCCGE8HG 2405685:HEXCEXFK 2405685:NBAIXDE4 2405685:XMGEKJ3V
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Pakistan Landscape Analysis Inception Report: UNICEF Inception Report - EdTech Hub Team (EdTech Hub, 2022)
Based on the growing access to technology, and the lessons learned from the experiences during the Covid-19 school closures, the Ministry of Federal Education and Professional Training (MoEFPT) has identified the formalisation of a strategy to develop and implement technology-based learning approaches as an immediate national priority. UNICEF Pakistan is developing a strategy to guide its engagement in the technology-facilitated learning space in Pakistan. This strategy will identify how both low- and high-tech learning modalities can be scaled to improve access to and the quality of learning for all Pakistan’s children and adolescents, including the most marginalised. This strategy will be underpinned by a rigorous review of the technology-enhanced learning landscape in Pakistan. EdTech Hub has supported governments and development partners globally to research, design, implement, and evaluate EdTech-related programmes to support education service delivery both during school closures and since reopenings have commenced. EdTech Hub will support UNICEF to undertake the aforementioned landscape review, focused specifically on EdTech tools that are being used for student learning in Pakistan. EdTech Hub will then collaborate with UNICEF to develop a strategy for UNICEF’s engagement in the technology-facilitated learning arena. This inception report sets out the scope of work for this partnership. The remainder of the report contains the following sections. Keywords:marginalised learners; EdTech tools; Pakistan; UNICEF; inception report; MoFEPT An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5032936 10.5281/zenodo.5142392 10.53832/edtechhub.0094 2405685:G9DHSZ57 2405685:HL6BNMQZ
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Learning Continuity in Response to Climate Emergencies: Preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
This resource is based on preliminary insights from EdTech Hub’s emerging study of Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders to identify feasible ways of using EdTech in response to Pakistan’s 2022 floods. The design adopted for this resource balances generating primary insights from flood-affected parents and teachers quickly and complementing these with insights from the existing evidence base on education in emergencies globally and nationally. EdTech Hub’s study of learning continuity in response to climate emergencies is ongoing. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7326483 ZenodoArchiveConcept: 7326482 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7326483 10.53832/edtechhub.0134 2339240:JZC2BLQQ 2405685:FKCF86HV 2405685:IHTU7JRT 2405685:UXWWBVVX
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Desk Review of Technology-Facilitated Learning in Pakistan: A review to guide future development of the technology-facilitated learning space in Pakistan - Wilson, Sam; Khalayleh, Abdullah; Baloch, Imdad; Kaye, Tom (EdTech Hub, 2022)
During the Covid-19 pandemic, EdTech has been used in many different ways to keep children learning in Pakistan. This has ranged from educational radio broadcasting to children in remote mountains, to TV channels being used to deliver classes nationwide. Yet, as the pandemic has developed, this picture has become more complex. Optimism in EdTech’s promise has given way to fears that the most marginalised children — particularly those who cannot access technological solutions — are falling further behind. Even those children who are able to use EdTech may not be learning. In short, a pre-existing digital divide has become more pronounced now that education delivery has had to increasingly rely on technology. This divide must be addressed if EdTech is to support effective learning for all children in all contexts in Pakistan. This desk review argues that the only way to realise EdTech’s potential is to recognise its shortcomings. Technology alone will not help children learn. EdTech’s role is as one part of a wider education system. Technology facilitates learning with support from key actors such as parents, teachers, and school leaders and with sustained political support and supporting infrastructure. This review provides an overview of Pakistan’s technology-facilitated learning landscape that caters to the learning needs of children aged 6–16. It sets out key EdTech-related features, challenges and trends, in addition to highlighting prominent EdTech organisations and tools in Pakistan. Keywords: infrastructure; low tech; policy; out-of-school children; marginalised learners; Pakistan; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5849102 10.53832/edtechhub.0071 2339240:5YT7LKSS 2405685:6FN5VTP7 2405685:8UMQILZ9 2405685:GMA7II34 2405685:WEG87IDU
Keywords: _r:AddedByZotZen

Support provided for K-12 teachers teaching remotely with technology during emergencies: A systematic review - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Samuel (Journal of Research on Technology in Education, 2021)
Emergencies can cause disruption to education. This study is unique in providing the first empirical systematic review on teacher support for Emergency Remote Education (ERE) from 2010 to 2020. A total of 57 studies emerged from the PRISMA search. This mixed-method study used deductive and inductive iterative methods to examine the data. The data reveal teacher support strategies from across 50 different high and low-income countries. Few studies focused on a teacher’s subject and the age range taught. In the examination of professional development provided to prepare K-12 teachers to conduct ERE, eight codes emerged from the grounded coding as; 1) prior preparation, 2) understanding ERE, 3) needs analysis, 4) digital pedagogical strategies, 5) technology tools, 6) frameworks, 7) digital equity, and 8) mental wellness.
ZenodoArchiveID: 5652026 Publisher: Routledge _eprint: https://doi.org/10.1080/15391523.2021.1899877 KerkoCite.ItemAlsoKnownAs: 10.1080/15391523.2021.1899877 10.1111/bjet.13114 10.5281/zenodo.5652026 2339240:258WF4VH 2339240:RAP22KJU 2405685:5UAQ3N5K 2405685:BKMMRYCD 2405685:IA5XF32V 2405685:SU6FMBKT 2405685:XERPP4G9 2534379:UVB8PHFN
Keywords: COVID-19; Teacher education; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:CopiedFromEvLib; _yl:a; disasters; emergencies; emergency remote education; pandemic; remote education

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4776960 2339240:JASYN9AV 2339240:URJVJP9H 2405685:7QBDH9I4 2405685:MXMPWAA2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Using Blended Learning to Support Marginalised Adolescent Girls’ Education: A Review of the Evidence - Allier-Gagneur, Zoé; Chuang, Rachel; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
This topic brief reviews evidence about the use of blended learning to support the education of marginalised adolescent girls in low- and middle- income countries.
ZenodoArchiveID: 4762319 previousDOI: 10.5281/zenodo.4762319 previousDOI: 10.5281/zenodo.4762319 previousDOI: 10.5281/zenodo.3952069 10.5281/zenodo.3952069 2405685:7PYD5JNV 2405685:H3AI5F3C 2339240:ENEKVCE3 2129771:FX6TFDPQ 2129771:9Q4PMCJN 2486141:TE93MW3V KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3952069 10.5281/zenodo.4762319 10.53832/edtechhub.0009 2339240:MU9RJZS3 2339240:WG969BFI 2405685:7PYD5JNV 2405685:A7IA7VZZ 2405685:H3AI5F3C 2405685:XMDKD3TS
Keywords: F: Helpdesk response; H:Blended learning; L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; dode_eth-src-eth; dode_eth-trf2-dode

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
ZenodoArchiveID: 5652066 previousZenodoArchiveID: 3885606 previousshortDOI: 10/ghgnfw previousDOI: 10.5281/zenodo.3885606 EdTechHub.Copy: 2129771:VAP9K6BW EdTechHub.Copy: 2129771:VAP9K6BW shortDOI: 10/ghgnfw KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3885606 10.5281/zenodo.3885606 10.53832/edtechhub.0026 10/ghgnfw 2129771:IK97VLY8 2129771:MXTVUGAA 2129771:VAP9K6BW 2339240:2ZVLRPTQ 2339240:7PXTZ2FQ 2339240:ZE9V9N4R 2405685:8IJT433J 2405685:9TKV7H6E 2405685:BBLQFJKE 2405685:IDL75DHT 2405685:WMUEC2ZV 2405685:Z2VNN7ER
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
previousshortDOI: 10/ghgng8 previousDOI: 10.5281/zenodo.3874247 EdTechHub.Source: 2405685:VX7UW757 EdTechHub.Source: <this> 2339240:KPL424XH shortDOI: 10/ghgng8 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3874247 10.5281/zenodo.3874247 10.53832/edtechhub.0025 10/ghgng8 2129771:LBII97HZ 2339240:2R8Z34D2 2339240:FT2TLP7Q 2339240:G93JLKST 2339240:J7DSQVEZ 2339240:QSKUJUNV 2339240:YK2KWXPL 2405685:2D6GK36K 2405685:48AAKD33 2405685:7VFMN2XM 2405685:G7ZB68PJ 2405685:I5WKHBZI 2405685:TP5CQYPQ 2405685:VX7UW757 2405685:YEVYTSJA 2405685:ZUDWQVKI
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
ZenodoArchiveID: 4557019 PreviousDOI: 10.5281/zenodo.4477154 PreviousShortDOI: 10/ghgnf2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3901521 10.5281/zenodo.4557019 10/ghgnf2 2339240:3KCTC7UA 2339240:5B7T9LEG 2339240:K45TP2GI 2339240:NNZ9DD54 2339240:SIV6ZELZ 2339240:W3ALIEA9 2405685:397HVPFN 2405685:4M9GTG8I 2405685:5AWZGNCG 2405685:6EUNRYPS 2405685:E56IKGK2 2405685:E6DMTNLL 2405685:TXGBLY4U 2405685:UUNEJ7FS 2405685:W9JLL7JV
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH

Back-to-School Campaigns Following Disruptions to Education - Chuang, Rachel; Kaye, Tom; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk response focuses on back-to-school campaigns following disruptions to education, ensuring that children rapidly return to school as soon as it is safe and practical. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3878423 previousshortDOI: 10/ghgk6n previousshortDOI: 10/ghgk6n previousDOI: 10.5281/zenodo.3878423 previousshortDOI: 10/ghgk6n EdTechHub.Source: 2405685:DS66UGW4 EdTechHub.Source: <this> shortDOI: 10/ghgk6n KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3878423 10.53832/edtechhub.0019 10/ghgk6n 2129771:GKIQY5RP 2339240:29BIZJM5 2339240:WSA5X76N 2405685:4Z5W36SI 2405685:DS66UGW4 2405685:IS587WTH
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

A five-part education response to the COVID-19 pandemic - Haßler, Björn; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2020)
In March 2020, many countries began to close schools to slow the spread of coronavirus. Education leaders have subsequently launched rapid response programmes, implemented measures to support system recovery and explored long-term reforms. This paper proposes a five-part approach to guide education leaders through this process.
ZenodoArchiveID: 3756012 previousDOI: 10.5281/zenodo.3756012 EdTechHub.Source: 2405685:JLEWADHF EdTechHub.Source: <this> KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3756012 10.53832/edtechhub.0005 2129771:SB3DJ28L 2129771:XKGV4EYL 2339240:5FRH2GYG 2339240:97HNYI75 2339240:S82QHGKQ 2405685:JLEWADHF 2405685:JTYIWEJY 2405685:L8KCID8V 2405685:NLEUNMRZ 2405685:SCDLVVC7 2405685:YMZUYZ4Z 2486141:9MWJP6MS
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:i; _zenodo:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
The EdTech Hub received a request from the FCDO Bangladesh team to provide a topic brief identifying best practices from previous back-to-school campaigns following disruptions. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3865298 previousshortDOI: 10/ghgk6p previousshortDOI: 10/ghgk6p previousDOI: 10.5281/zenodo.3865298 shortDOI: 10/ghgk6p KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3865298 10.53832/edtechhub.0020 10/ghgk6p 2129771:2BEHBMUH 2129771:C6TREICJ 2129771:GQ4U9R5Z 2129771:QFFBWT4D 2339240:H8RZC7AY 2339240:T5DE93E2 2405685:3HP24UTI 2405685:CEADG684 2405685:H52W8E9M 2405685:HFKVA2IQ 2405685:U2AQUAZ2 2486141:B8P7D4EU
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _yl:g; _zenodo:submitted; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

The Use of Virtual Learning Environments and Learning Management Systems During the Covid-19 Pandemic - McBurnie, Chris (EdTech Hub, 2020)
This technical note aims to inform the use and development of virtual learning environments (VLE) in educational responses to the current health crisis. It considers the advantages and disadvantages of a number of existing VLEs and includes guidance on selecting an appropriate VLE.
ZenodoArchiveID: 5652169 previousZenodoArchiveID: 3805843 previousshortDOI: 10/gg7sqk previousDOI: 10.5281/zenodo.3805843 EdTechHub.Copy: 2129771:DQLDNQGU shortDOI: 10/gg7sqk KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3805843 10.5281/zenodo.3805843 10.53832/edtechhub.0023 10/gg7sqk 2129771:DQLDNQGU 2339240:IWW8CJZN 2339240:N5RG3WT2 2339240:QGMNZZER 2405685:53YEZE6A 2405685:933PQ5Q6 2405685:MHEB7LKZ 2405685:WBNK52L7
Keywords: COV:COVID and reopening of schools; COVID-19; Distance learning; EdTech; F: Helpdesk response; H: Distance education; LP: English; Learning management system; Remote learning; Virtual learning environment; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Education during the COVID-19 crisis: opportunities and constraints of using EdTech in low-income countries - David, Raluca; Pellini, Arnaldo; Jordan, Katy; Philips, Toby (Zenodo, 2020)
Key points: Technology can help mitigate the effects of the educational crisis and closures of schools, but ed-tech is not a silver bullet and governments need to have realistic expectations about what it can achieve The digital divide means that internet and mobile network access varies greatly in middle- and low-income countries Governments can provide immediate support by informing teachers about simple grassroots platforms where they can share their own ed-tech solutions Educational TV and radio broadcasts in combination with SMS are effective communication channels between educators and students when the internet connectivity is poor or not available It will be important for education authorities to begin planning how in 12-months’ time they will diagnose and treat the learning gaps that have emerged during the crisis.
shortDOI: 10/ghgnd7 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3750976 10/ghgnd7 2339240:3CKN9C4K 2339240:5AHKKQF6 2405685:92ZVGWNU 2405685:CT8JMZEU
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodoETH; covid-19; crisis education; distance education; education; education policy; educational technology; emergency education; pandemic education; school closures; schools

Summarised Findings from the EdTech Hub Helpdesk - Chuang, Rachel; Moss Coflan, Caitlin (EdTech Hub, 2020)
As of December 2020, EdTech Hub’s Helpdesk has been active for nine months, responding to over 60 requests supporting decision-making on education technology. This document summarises our responses to six commonly asked questions across the topics of reaching marginalised learners, supporting teachers, and using EdTech to mitigate learning loss.
previousDOI: ​10.5281/zenodo.4299931 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4299931 10.5281/zenodo.4768560 2339240:CYPLQHH4 2405685:C49UMTX2 2405685:CWRFU9K9
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:image; _r:CopiedFromEvLib; _zenodoETH; _zenodoETH:submitted

Accelerated Learning and EdTech: A Rapid Evidence Review - Damani, Kalifa (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of accelerated learning in low- and middle-income countries (LMICs), with a focus on how EdTech might best be utilised for accelerated learning. It begins with a broad discussion of the components of accelerated learning, followed by a more focused discussion on how accelerated learning has been used to enhance learning outcomes for marginalised groups in LMICs. An exploration of how EdTech can be utilised for accelerated learning is then presented.
ZenodoArchiveID: 4556941 Note: This item replaced a previous version with DOI 10.5281/zenodo.4071441. PreviousDOI: 10.5281/zenodo.4071441 PreviousDOI: 10.5281/zenodo.4477135 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4556941 10.5281/zenodo.4071441 10.5281/zenodo.4477135 10.5281/zenodo.4556941 2339240:785U4JZJ 2339240:9MZRHWYE 2339240:TQLWMAIZ 2405685:9BWHLEWZ 2405685:I4UFGAQA 2405685:JV5JCGN3 2405685:XNYSHYYD
Keywords: L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

EdTech Innovation for COVID-19: Insights from our global call for ideas - Plaut, Daniel; Carter, Alice; Dixon, Miranda; Salami, Taiye (EdTech Hub, 2020)
ZenodoArchiveID: 4768571 previousDOI: 10.5281/zenodo.4277895 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4277895 10.5281/zenodo.4768571 2339240:5M4KPPAH 2339240:MQLLLDAJ 2405685:S7JARBXV 2405685:T2HBLDU6 2405685:TE7A3D6X
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH

EdTech in Senegal: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
ZenodoArchiveID: 5652140 previousZenodoArchiveID: 3936687 previousshortDOI: 10/ghgnd2 previousDOI: 10.5281/zenodo.3936687 shortDOI: 10/ghgnd2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3936687 10.53832/edtechhub.0037 10/ghgnd2 2339240:EHTSKIBR 2339240:YQHNWNMB 2405685:5P5HVP47 2405685:BBP57X2K 2405685:SKFMQF3F 2405685:XI5PXVB3
Keywords: C:Senegal; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; pu

Education in Emergencies: A Rapid Evidence Review - Mitchell, Joel; Ashlee, Amy; Clericetti, Giulia; Gladwell, Jessica; Torrance, Rebecca (EdTech Hub)
PreviousDOI: 10.5281/zenodo.4476897 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4476897 10.5281/zenodo.4556940 2339240:GU8FEH69 2339240:W9GJBGT9 2405685:FEXJQ37Q 2405685:ZPTMAP5C
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
ZenodoArchiveID: 7267302 ZenodoArchiveConcept: 7267301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7267302 10.53832/edtechhub.0127 2339240:V7ARHU93 2405685:GBBGHCBH 2405685:QADQUWU3 2405685:UTTZNZ24
Keywords: _r:AddedByZotZen

EdTech to Support Out-of-School Children and Adolescents - Thinley, Sangay; Rui, Yang (EdTech Hub, 2023)
This Helpdesk report was created in response to a request from the World Bank Malawi Education Team for a curated list of resources on examples of EdTech interventions targeting out-of-school children and adolescents to inform an ASA (Advisory Services and Analytics) output. The ASA output will provide policy options to improve second-chance learning and foundational skills for out-of-school children (OOSC). To provide the World Bank Malawi team with adequate information on the above. This curated list begins with an introduction to the use of EdTech to support out-of-school children and youth, and then moves on to present examples of such interventions and programmes within Malawi, as well the wider African region and the rest of the world. This list is designed to serve as a resource for the team and does not make any direct recommendations on actions to be taken. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7906889 ZenodoArchiveConcept: 7906888 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7906875 10.5281/zenodo.7906889 10.53832/edtechhub.0163 2339240:2LWVXYCV 2405685:4CB23ZC6 2405685:AG764A26 2405685:VWJXTPI8
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

The Sandbox Model: A Novel Approach to Iterating while Implementing an Emergency Education Program in Lebanon during the COVID-19 Pandemic - Boujikian, Michèle; Carter, Alice; Jordan, Katy (2022)
Jusoor’s Refugee Education Program helps Syrian refugee children living in Lebanon integrate back into formal schooling. When schools closed due to the COVID-19 pandemic, the refugee program adapted to distance learning by developing Azima, a novel program that used WhatsApp to enable children to keep learning. Azima had to respond immediately to the emergency context while maintaining high education standards, and it also needed to find an effective way to test and refine its content quickly. To do this, the Azima program adopted an innovative experimental approach called a sandbox. A sandbox model operates in rapid iterative cycles and uses multiple methods to quickly test a program’s assumptions about how it will meet its goals. In this field note, we use Azima as a case study to report on our experience of applying the sandbox model. We reflect on the benefits and limitations of this novel approach in supporting the use of education technology in a crisis situation.
Accepted: 2022-11-07T13:27:21Z Publisher: Inter-agency for Education in Emergencies (INEE) KerkoCite.ItemAlsoKnownAs: 10.33682/rj45-k7z7 2405685:LDWAQKHF

Covid-19 school closures in low- and middle-income countries: Emergent perspectives on the role of educational technology - Jordan, Katy (Journal of Learning for Development, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:2BDLYTUP 2339240:DFHS5PI3 2339240:JTUAX3R7 2339240:V7VSHKVT 2405685:AVYK5T2I 2405685:BVFLF8QP 2405685:J7AK3RMI 2405685:JV429XI7
Keywords: COVID-19; ___working_potential_duplicate; digital divide; education in emergencies. education systems; educational technology; ⛔ No DOI found